2020
DOI: 10.48550/arxiv.2001.02443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordination of Autonomous Vehicles: Taxonomy and Survey

Stefano Mariani,
Giacomo Cabri,
Franco Zambonelli

Abstract: In the near future, our streets will be populated by myriads of autonomous self-driving vehicles to serve our diverse mobility needs. This will raise the need to coordinate their movements in order to properly handle both access to shared resources (e.g., intersections and parking slots) and the execution of mobility tasks (e.g., platooning and ramp merging). In this paper, we firstly introduce the general issues associated to coordination of autonomous vehicles, by identifying and framing the key classes of c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…For example, Hult et al (2020) showed how level-5 ADSs can cooperate at an intersection by first solving a mixedinteger quadratic program to identify vehicle crossing order and subsequently solving a nonlinear program to determine vehicle control inputs. An extensive survey and discussion of such coordination research in higher level ADSs is provided by Mariani et al (2020). Conversely, the anticipated gradual incorporation of ADSs worldwide presents a unique challenge: MVs and ADSs will likely cohabit roadways for a substantial period of time.…”
Section: Heterogeneous Trafficmentioning
confidence: 99%
“…For example, Hult et al (2020) showed how level-5 ADSs can cooperate at an intersection by first solving a mixedinteger quadratic program to identify vehicle crossing order and subsequently solving a nonlinear program to determine vehicle control inputs. An extensive survey and discussion of such coordination research in higher level ADSs is provided by Mariani et al (2020). Conversely, the anticipated gradual incorporation of ADSs worldwide presents a unique challenge: MVs and ADSs will likely cohabit roadways for a substantial period of time.…”
Section: Heterogeneous Trafficmentioning
confidence: 99%
“…where parameter q ij = 1 if agent i is qualified to perform task j, 0 otherwise, parameter p ij is the utility of assigning agent i to task j (with p ij = 0 if q ij = 0), and variable x ij = 1 if agent i is assigned to task j, 0 otherwise. Constraints (6) ensure that no more than one qualified agent is assigned to any task, while constraints (7) guarantee that each agent is assigned to not more than one task. The classic assignment problem does not consider fairness.…”
Section: The Classic Assignment Problem Recognizing Agent Qualificati...mentioning
confidence: 99%
“…Even though some works exist that include reviews of the state of the art in multi-agent task allocation (see, e.g., [2,3,4,5,6]) and in vehicle fleet coordination (see, e.g., [7,8,9]) or ridesharing optimization (see, e.g., [10,11]), none of them addresses one-on-one dynamic task assignment problems in open vehicle fleets. In addition, a few approaches apply methods of multi-agent task allocation to the field of vehicle fleet coordination (see, e.g., [12]) but, to the best of our knowledge, there is no systematic survey combining both fields.…”
Section: Introductionmentioning
confidence: 99%